Generic hierarchy of sandstone facies quality and static connectivity: an example from the Middle-Late Miocene Miri Formation, Sarawak Basin, Borneo - Siddiqui, N.A. (Springer Verlag, 2017)
A significant percentage of the world’s hydrocarbon reserves are found in shallow marine sandstone rocks. Understanding reservoir connectivity and quality of shallow-marine sandstones from outcrop analysis and facies characteristics is a challenging task. Here, we analyze well-exposed outcrops of the Miri Formation, Sarawak Basin, Borneo, to characterize reservoir properties (grain-size, petrography, pore-perm, and static connectivity) of different sandstone facies and to construct a 2D intermediate-scale model of sandstone distribution and connectivity. The outcrops, with lateral extent of ∼200–500 m, consist of mostly sandstone with mud-rich deposits including some isolated sand bodies. Field description in terms of facies distribution and dimensions of sand bodies and rock sampling for grain-size (Folk and Ward methods), petrographic (point count method for porosity, sorting, grain-size, and sand-mud ), and poro-perm (for porosity and permeability) analyses were performed to quantify and examine seven different types of sandstones facies, i.e., (i) hummocky cross-stratified sandstones (HCSS, ∼0.5–4 m thick), (ii) herringbone cross-bedded (HBCBS, ∼0.5–3 m thick), (iii) trough cross-bedded sandstones (TCBS, ∼0.5–2 m thick), (iv) wavy- to flaser-bedded (W-FBS, ∼1–3 m thick), (v) cross-bedded sandstone (CS), ∼0.5–3 m thick), (vi) bioturbated sandstone (BS, ∼1–5 m thick), and (vii) massive sandstone (MS, ∼0.5–2 m thick). Our results show that compared to other sandstone facies, sandstones of HCSS and HBCBS are better sorted, have minimal mud content, and display increasing vertical and lateral connectivity due to depositional patterns even in bioturbated rich sand. Sandstones of BS and CB are of poor quality in terms of grain sorting and poro-perm, while TCB and MS sandstone facies are of less lateral and vertical extent. On the basis of these results, a 2-D outcrop-based model is constructed that provide additional insights into the significance of small-scale heterogeneity and static connectivity of shallow marine sandstone deposits which can be an analogue for subsurface reservoir quality analysis. © 2017, Saudi Society for Geosciences.